Partial stem resistance in Brassica napus to highly aggressive and genetically diverse Sclerotinia sclerotiorum isolates from Australia - Denton-Giles, Matthew; Derbyshire, Mark; Khentry, Y.; Buchwaldt, L.; Kamphuis, Lars (2018)
Sclerotinia sclerotiorum is a fungal pathogen that causes stem rot in oilseed rape (Brassica napus). Previously, B. napus accessions with partial stem resistance to a Canadian S. sclerotiorum isolate (#321) were identified using a stem test in which flowering plants were inoculated with mycelium plugs. The present study examined the partial stem resistance of four of these accessions, PAK54, PAK93, DC21 and K22, following inoculation with Australian isolates. Mycelial compatibility groups and intergenic spacer (IGS) region haplotypes were identified among 71 isolates from Australian oilseed rape and lupin fields. Eleven genetically diverse isolates showed differences in aggressiveness when inoculated onto nine oilseed rape varieties and one Chinese accession. Isolates CU8.24, CU10.17 and CU11.19 were selected based on genetic diversity, growth rate in vitro and high aggressiveness in the initial screen and subsequently inoculated onto the four B. napus accessions. These accessions developed significantly smaller lesions compared with the susceptible control varieties (‘AV Garnet’ and ‘Westar’), with the average frequency of soft and collapsed lesions being less than 20% in PAK54, DC21 and K22, 29% in PAK93 and greater than 88% in the susceptible controls. Microscopic examination revealed that hyphae were typically confined to the stem cortex in the smallest lesions, but could be found in the stem pith in larger lesions. These results show that B. napus accessions PAK54, PAK93, DC21 and K22 can be used in Australia for development of varieties with partial stem resistance to S. sclerotiorum.